Pemberdayaan Kemampuan Berpikir Kritis Siswa melalui Implementasi Model Pembelajaran Think Talk Write dipadu Problem Based Learning - Lidya Yanuarta; Abdul Gofur; Sri Endah Indriwati (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2016)
Critical thinking is a complex reflection process that helps individuals become more analytical in their thinking. Empower critical thinking in students need to be done so that students can resolve the problems that exist in their life and are able to apply alternative solutions to problems in a different situations. Therefore, Think Talk Write (TTW) combined Problem Based Learning (PBL) were needed to empowered the critical thinking skills so that students were able to face the challenges of the 21’st century. TTW combined PBL is a learning model that is expected to empower the students critical thinking skills. The purpose of this research was to determined the effect of TTW combined PBL to the students critical thinking skills. The research is a quasi-experimental with Nonequivalent Pretest-Posttest Control Group Design. Samples were X MIPA 1 and X MIPA 2 in SMAN 6 Malang. Data obtained from the critical thinking skills essay test. The data were analyzed using Anacova test. The results showed that learning biology with TTW combined PBL learning model can effect on students critical thinking skills. Keywords:     Think Talk Write, Problem Based Learning, Critical Thinking Skills